Insights into the metagenomic and metabolomic compositions of the bacterial communities in Thai traditional fermented foods as well as the relationships between food nutrition and food microbiomes - Pongrawee Nimnoi; Neelawan Pongsilp (PeerJ, 2025)
Five Thai traditional fermented foods, including khao-mak (sweet fermented sticky rice), pak-kard-dong (sour salt-fermented mustard greens), nor-mai-dong (sour salt-fermented bamboo sprouts), moo-som (sour salt-fermented pork), and pla-som (sour salt-fermented fish), were analyzed for their food nutrition and bacterial community structures. Sour salt-fermented bamboo sprouts possessed the highest unique amplicon sequence variables (ASVs), which were 3,476, as well as the highest bacterial diversity and richness, while in contrast, sweet fermented sticky rice possessed the lowest such indices. The phylum Firmicutes accounted for the largest proportions in both sour salt-fermented meats and sweet fermented sticky rice whereas the Proteobacteria occupied the largest proportions in both sour salt-fermented vegetables. The bacterial community structures of both sour salt-fermented meats were similar in terms of composition at class level, while the dominant genera compositions were totally different among all foods. Gene functions, enzymes, and metabolic pathways annotated from the bacterial communities in all foods were those involved in growth metabolisms, genetic information processing, environmental information processing, and cellular signaling. Sour salt-fermented bamboo sprouts had the highest numbers of unique annotated genes, enzymes, and metabolic pathways.